Teacher’s Effort In Increasing Students’ Motivation For Learning Speaking For The Eigth Graders Of Smp Lab. Hamzanwadi Pancor In The School Year 2022/2023 - Mas, Dzoharat Nabilah (International Conference on Islamic Studies, 2022)
The background of this research was how to increasing students’ learning English speaking motivation, a factor that also influences student success in speaking English. Students with great motivation in speaking English will be able to carry out all their learning activities seriously, students learning English speaking at SMP Lab. Hamzanwadi Pancor was quite good, it can be seen from the many trophies won and displayed in front of the teacher's room at SMP Lab. Hamzanwadi Pancor and their enthusiastic students when participating in the learning English speaking teaching and learning process. This study aimed to find out how the efforts made by SMP Lab. Hamzanwadi Pancor teachers in increasing students' learning English speaking motivation. This research was qualitative research that took place at SMP Lab. Hamzanwadi Pancor. Data collection was carried out by observation, interviews and documentation. Research subjects were people who know, relate to and become actors of an activity that was expected to provide information. Data analysis was carried out by giving meaning from the data collected, and from that meaning conclusions were drawn. The result of this study was to find out how the efforts made by the teacher in increasing students' learning English speaking motivation at SMP Lab. Hamzanwadi Pancor. The efforts made by teachers in increasing learning English speaking motivation include: explaining learning objectives to students, linking lessons with past lessons, using learning media, changing learning places, providing opportunities for students to ask questions, providing practice questions, assignments and homework. giving value to student work, holding competitions, giving praise, and giving reprimands.